2019
DOI: 10.1136/bmjophth-2019-000326
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids supplementation protects the retina from age-associated degeneration in aged C57BL/6J mice

Abstract: ObjectiveTo evaluate the therapeutic effects of omega-3 (ω3) fatty acids in the retina of aged mice when the blood arachidonic acid (AA)/eicosapentaenoic acid (EPA) ratio is maintained between 1.0 and 1.5.Methods and analysisAged (24-month-old) wild-type C57BL/6J mice were allocated to two groups: ω3 treated and untreated. Treatment with ω3 was by daily gavage administration of EPA and docosahexaenoic acid for 60 days. Gas chromatography was used to identify and quantify fatty acids in the blood and retina. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Previous studies found no or marginal increases in retinal omega-3 levels even after treatment with very high concentrations of dietary omega-3 FA. For example, Prokopiou et al [ 40 ] fed aged (2-year-old) mice 200 mg omega-3 FA/day in the form of fish oil for 60 days, and found actually a decrease in retinal DHA (−21%), although retinal EPA, which is a minor constituent, increased by 42%. Similarly, gavaging ABCA4−/− mice (Stargardt disease) with 206 mg/day of omega-3 FA (172 mg EPA + 34 mg DHA) for three months resulted in no change in retinal DHA, although a 67% increase in retinal EPA (from 0.93% to 1.56% of total) was observed [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found no or marginal increases in retinal omega-3 levels even after treatment with very high concentrations of dietary omega-3 FA. For example, Prokopiou et al [ 40 ] fed aged (2-year-old) mice 200 mg omega-3 FA/day in the form of fish oil for 60 days, and found actually a decrease in retinal DHA (−21%), although retinal EPA, which is a minor constituent, increased by 42%. Similarly, gavaging ABCA4−/− mice (Stargardt disease) with 206 mg/day of omega-3 FA (172 mg EPA + 34 mg DHA) for three months resulted in no change in retinal DHA, although a 67% increase in retinal EPA (from 0.93% to 1.56% of total) was observed [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing scientific evidence highlights the crucial role of diet (48), probiotics (49) and nutraceutical (50) products on biological processes (pathogen resistance, xenobiotic and drug metabolism, delay in the aging process, prevention of chronic diseases, increase in life expectancy, or support in the structure or function of the body) and, consequently, on human health and diseases, including cancer (51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Small amounts of by‐products are able to induce antioxidative responses, for example, by inducing nuclear factor erythroid 2–related factor 2 (Nrf‐2) activity (Tanito & Anderson, 2017). In aged mice, omega fatty acid (eicosapentaenoic acid and docosahexaenoic acid) supplementation has been shown to slow down the degeneration of the retina as well as protecting neural progenitor cells from oxidative stress (Prokopiou et al, 2019). Omega fatty acids belong to the natural antioxidative system of the retina and protect the retina from oxidative stress‐related damages, enhance the activity of other antioxidative mechanisms, for example, glutathione activity and have anti‐inflammatory properties (Lafuente et al, 2021).…”
Section: Review Of the Literaturementioning
confidence: 99%